The Contribution Hypoalbumin Status on Diagnosing LF-LAM TB Ag Versus Xpert MTB/Rif in Patients Pulmonary Tuberculosis - Eksa, Dwi Robbiardy; Hendarto, Gatot Sudiro; Sinaga, Fransisca Tarida Yuniar; Dilangga, Pad; Herdato, M. Junus Didiek; Infianto, Andreas; Ekawati, Diyan; Gozali, Achmad; Ajipurnomo, Adhari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
In 2023, the global prevalence of tuberculosis (TB) reached 8.2 million cases. This represents the highest recorded figure associated with delayed diagnostics and a rising incidence of tuberculosis cases. Tuberculosis prevalence is elevated among individuals with compromised immune systems, including those with HIV and hypoalbuminemia, who exhibit increased vulnerability to infection. The challenge of sputum ejection impedes diagnosis, highlighting the need for a rapid and economical early detection method. The LF-LAM TB-Ag assay provides an alternative method for determining the presence of Lipoarabinomannan in urine, which is a component of the Mycobacterium tuberculosis cell wall. This study evaluated the efficacy of the LF-LAM TB-Ag assay compared to the Xpert MTB/RIF method for diagnosing tuberculosis. A comparative cross-sectional study was conducted at Abdoel Moeloek Hospital in Lampung Province, Indonesia, between January 2023 and June 2024. A total of 52 suspected pulmonary tuberculosis patients, who were HIV-negative and had hypoalbumin status, were evaluated using both the LF-LAM TB-Ag and Xpert MTB/RIF assays. The Wilcoxon and Chi-square tests have been utilised to assess the efficacy of LF-LAM TB-Ag in comparison to Xpert MTB/RIF. A p-value below 0.002 was considered statistically significant. Xpert MTB/RIF demonstrated improved diagnostic accuracy for tuberculosis in individuals with hypoalbuminemia. This study emphasises the necessity for early detection of pulmonary tuberculosis in patients with hypoalbuminemia. The combining of LF-LAM TB-Ag with Xpert MTB/RIF improves detection, especially among high-risk populations, thereby enabling prompt treatment and enhanced disease management.